Hepatic sinusoidal obstruction syndrome/veno-occlusive disease after hematopoietic cell transplantation: historical and current considerations in Korea - Jae-Ho Yoon (The Korean Association of Internal Medicine, 2021)
Hepatic sinusoidal obstruction syndrome/veno-occlusive disease (SOS/VOD) is a rare but severe complication of hematopoietic cell transplantation (HCT) showing high mortality. Multiple risk factors for SOS/VOD were identified, but it is often confused with other hepatic complications due to nonspecific clinical features. Therefore, diagnostic and severity criteria have been revised several times. The European Society of Blood and Marrow Transplantation suggested a new guideline that excludes the standard duration of development within 21 days, emphasizes late-onset SOS/VOD, and suggests the importance of Doppler ultrasonography. The severity criteria were further subdivided for guidance to begin active treatment using defibrotide which was approved in Korea since 2016. In a phase 3 trial, defibrotide had superior 100-day survival, compared to best available treatments (38.2% vs. 25.0%). Although several studies of SOS/VOD in Korean patients have been performed after the implementation of HCT, most involved small number of pediatric patients. Recently, the Korean Society of Blood and Marrow Transplantation investigated the incidence of SOS/VOD in the Korean population, and several influential studies of adult patients were published. Here, we summarize recent issues regarding the mechanism, diagnosis, severity criteria, prevention, and treatments of SOS/VOD in Korean patients, as well as recent analyses of nationwide incidence.